Nutrient Disequilibria in Agroecosystems: Concepts and Case Studies - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Edited by E M A Smaling (Wageningen UR, Laboratory of Soil Science and Geology, The Netherlands), O Oenema (Wageningen UR, Research Institute for Agrobiology and Soil Fertility, The Netherlands), and L O Fresco (Sustainable Development, FAO, Italy)....